Using Job Sheet in Learning Ship Welding Techniques to Increase Learning Achievement of Class X Vocational School Students - Nur'alifah, Sri (Science Education and Application Journal, 2022)
There is a need for media in the learning process to improve student achievement. The purpose of this study was to determine the model of using job sheets in learning welding techniques in class X TPK SMKN 2 Lamongan. And to find out the learning achievement of students after the job sheet model is implemented. The subjects of this study were students of class X TPK SMKN 2 Lamongan. This classroom action research procedure uses 3 (three) cycles. Each cycle consists of 3 (three) stages, namely: (1) planning; (2) action and observation; (3) reflection, according to the model developed by Kemmis and Mc Taggart. The instruments used to collect data are: (1) lesson plans; (2) pretest-posttest question sheets, (3) practice result assessment sheets (4) student practice observation sheets (5) learning management observation sheets; and (6) daily journal. The results showed that an increase in student learning achievement can be seen from the average value of student learning achievement starting from the pretest, cycle I, cycle II and cycle III, respectively 5.35; 6.78; 7.65; 7.92 with Gain (increase) in each successive cycle of 1.43; 0.87 and 0.27. The percentage of the average value of learning management for aspects of teacher activities increased by 13% from 68% in the first cycle to 81% in the second cycle and increased 5% from 81% in the second cycle to 86% in the third cycle.